Hematology Profiles in Colorectal Cancer Patients in Bali - Kurniawati, Ida; Dewi, Anak Agung Ayu Asri Prima; Kerans, Fransiscus Fiano Anthony; Witari, Ni Putu Diah; Adyasputri, A A I Ayesa Febrinia; Sueta, Made Agus Dwianthara; Sumadewi, Komang Trisna; Evayanti, Luh Gde; Astini, Dewa Ayu Agung Alit Suka (Jurnal Ilmiah Kesehatan, 2025)
Colorectal cancer is a leading cause of cancer-related deaths worldwide. This study explores blood profile and cancer staging in colorectal cancer patients in Bali. It was a descriptive-analytical study that collected demographic and clinical data from medical records of colorectal cancer patients at Prof. Dr. I.G.N.G. Ngoerah Hospital. The results of the study showed the basic characteristics and hematology profiles of 100 colorectal cancer patients. The average age of patients was 55.6 ± 11.4 years, with 54% of the total sample being male. The average body mass index (BMI) was 21.1 ± 3.6 kg/m², with an average height of 161.9 ± 6.1 cm and an average weight of 55.3 ± 10.0 kg. Laboratory tests revealed an average hemoglobin (Hb) level of 11.0 ± 3.6 g/dL, red blood cell count of 4.0 ± 0.9 million/μL, white blood cell count of 11.2 ± 7.3 thousand/μL, and platelet count of 302.8 ± 154.8 thousand/μL. The average hematocrit (HCT) level was 33.7 ± 6.6 L/L. Liver function parameters indicated average aspartate aminotransferase (AST/SGOT) levels of 45.6 ± 63.6 U/L and alanine aminotransferase (ALT/SGPT) levels of 24.6 ± 29.4 U/L. Renal function was described by an average blood urea nitrogen (BUN) level of 21.8 ± 21.0 mg/dL, urea levels of 21.9 ± 21.2 mg/dL, and creatinine levels of 2.3 ± 11.5 mg/dL. Our study highlights the importance of hematology profiles in colorectal cancer patients as part of cancer screening examination. Further study with a larger number of samples and more diverse populations is needed to analyze the relation between variables.